Differential approach to arterial hypertension treatment in pregnancy - T. E. Belokrinitskaya; A. P. Filev; V. S. Barkan (Российский кардиологический журнал, 2006)
The aim of the study was to compare effects of selective beta-1-adrenoblocker metoprolol (corvitol), clophelin (clonidine) and dopegyt (methyldopa) on mother's hemodynamics and feto-placental complex state. In total, 60 pregnant women with Stage II essential arterial hypertension (AH), and 20 healthy pregnant women of similar age and gestation duration, were examined. The patients were divided into three clinical groups: Group I received metoprolol (50 mg twice per day; after blood pressure (BP) stabilization - 25 mg/d), Group II - clophelin (0, 075 mg 2-3 times per day), Group III - dopegyt (250 mg twice per day). Treatment effectiveness was assessed by mother's echocardiography, feto-placental vessel dopplerometry, fetal cardiotocography, placental histology. In hypertensive women with hyperkinetic hemodynamics, metoprolol more effectively, than clophelin and dopegyt, reduced BP, normalized mother's central hemodynamics, restored feto-placental blood flow, and increased fetal cardiovascular system reactivity. Clophelin was clinically effective in patients with hypokinetic central hemodynamics, dopegyt - in women with eukinetic hemodynamics. Antihypertensive therapy in pregnant women with essential AH should be differential, according to central hemodynamics type.